Pengaruh Penggantian Sebagian Ransum Komersil dengan Bungkil Kelapa Hasil Fermentasi dengan Effective Microorganism-4 (Em-4) terhadap Bobot Karkas Ayam Pedaging - Mairizal Mairizal (Jurnal Peternakan Indonesia (Indonesian Journal of Animal Science), 2013)
This study aimed to examine the effect of partial replacement of commercial ration with fermented coconut meal with effective microorganism-4 (EM-4) on the carcass weight of broilers. This study used 100 chicks aged 3 days old. The design used was a completely randomized design (CRD) with 5 kinds of treatment of rations containing 0, 5, 10, 15 and 20% coconut meal fermented with EM-4 under four replications. Chickens reared for 4 weeks and at the end of the study two chickens were taken from each unit of the cage to cut and the carcas were analyzed. Parameters observed were feed intake, slaughter weight, and percentage of carcas. The data were processed using analysis of variance with Duncan's advanced test. The results showed that the use of coconut meal fermented with EM-4 in the ration of broiler was significant (P <0,05) in reducing feed intake and slaughter weight but it had no significant effect (P> 0,05) on the percentage of carcass weight. It was concluded that the use of coconut meal fermented with EM-4 in broiler rations may be used only to the extent of 15%.